ANALYSING TEACHER’S DIFFICULTIES IN TEACHING LISTENING - Suhud Aryana; Yanuarti Apsari (STKIP Siliwangi, 2018)
This research is based on the importance of listening skill for students at Senior High School especially twelfth grade, because they will face the National Examination. As one of English skill, listening is the most difficult skill to be taught and this process cannot be avoided by all teachers who teach English. Moreover, some teachers still get difficulties how to teach listening to students and this research is focused on Analyzing Teacher’s Difficulties in teaching listening. In this research, the writer used case study and qualitative research method. The subject of this research was one of an English teacher at MA Islahul Aqidah Cikalongwetan West Java. The instruments of this research are observation, interview and questionnaire. In short, the results of this research showed that teacher’s difficulties divided into two factors, those are internal and external factors. Internal factors which came from the respondent himself such as; he feels the difficulties in teaching, preparing listening materials, choosing method, technique, and strategy. External factors are; sound from environment activities like woodcutter machine, module, media problem as cable injector of sound system to laptop, English laboratory, electric off, and the difference of listening materials in syllabus 2013 curriculum and National Examination materials.